MODEL MATHEMATICAL PROBLEM SOLVING DENGAN STRATEGI KONFLIK KOGNITIF: SEBUAH MODEL PEMBELAJARAN UNTUK MELATIHKAN KEMAMPUAN ANALYTICALDECISION MAKING MAHASISWA CALON GURU - Sukarma, I Ketut (Jurnal Ilmiah IKIP Mataram, 2019)
Analytical decision making is very important because it becomes the ultimate goalÂ inÂ learning. Analytical decision-making and objectives for making decisions based on the results of an analysis of information, data or facts, and phenomena, development models used to make analytical decisions. This study aims to develop a model of Mathematical Problem Solving with Conflict Cognitive Strategy to train the analytical decision-making ability of prospective teachers. This research is a development research that produces a valid model learning that is Mathematical Problem Solving with Conflict Cognitive Strategy to train analytical decision-making ability of the prospective teacher. The result of validity test obtained through focus group discussion activity shows that the developed model is valid. Components of validity that consist of content validity and constructs validity results are: 1) need: 4.55 (very valid); 2) state of the art: 4.45 (very valid); 3) construct: 4.4 (very valid). Meanwhile, the supporting learning devices developedÂ includeÂ the lesson plan, Module, worksheet, and analytical decision analysis instrument are valid with average score 3.6 and 0.97 of reliability with the reliable category. Based on these results it can be concluded that the Mathematical Problem Solving model with Conflict Cognitive Strategy and it supporting learning device valid to train the analytical skills of Prospective teacher decision making.